2006
DOI: 10.1177/154405910608500209
|View full text |Cite
|
Sign up to set email alerts
|

Articaine is More Effective than Lidocaine or Mepivacaine in Rat Sensory Nerve Conduction Block in vitro

Abstract: The reasons for the relatively high failure rate after inferior alveolar nerve block in dentistry are not fully understood. Therefore, the effectiveness of different anesthetic solutions (2% and 4% lidocaine, 3% mepivacine, 2% and 4% articaine) in depressing the compound action potential amplitude of the sensory fibers in the rat sural nerve was examined under strictly controlled conditions in vitro. After application of an anesthetic solution and stimulation of the nerve with a supramaximal electrical stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
4
21
1
14
Order By: Relevance
“…This was in accordance to Rebolledo et al [50]. Potonick et al [45] reported that 2 % Articaine more effectively depresses the compound action potential of the A fibers in the isolated rat sural nerve than either 2 % or 4 % Lidocaine or 3 % Mepivacaine. Paessler et al [46] concluded that the 4 % Articaine solution did not prove superior in local anesthetic effect.…”
Section: Efficacy Of Articainesupporting
confidence: 91%
See 1 more Smart Citation
“…This was in accordance to Rebolledo et al [50]. Potonick et al [45] reported that 2 % Articaine more effectively depresses the compound action potential of the A fibers in the isolated rat sural nerve than either 2 % or 4 % Lidocaine or 3 % Mepivacaine. Paessler et al [46] concluded that the 4 % Articaine solution did not prove superior in local anesthetic effect.…”
Section: Efficacy Of Articainesupporting
confidence: 91%
“…Malamed et al [8,9] reported overall incidence of adverse events in the combined studies was 22 % for Articaine and 20 % Lidocaine of which paresthesia was 0.9 %, hypoesthesia 0.7 %, headache 0.55 %, infection 0.45 %, rash and pain 0.3 %. Potonick et al [45] reported that although 4 % Articaine is more effective, they suggested that it may be worth considering replacing the 4 % Articaine with 2 % Articaine solution as the risk of an intravenous injection of the anesthetic solution during the induction of inferior alveolar nerve block and the possibility that the 4 % Articaine solution may increase the incidence of non surgical paresthesia. In our study, two patients experienced inferior alveolar nerve paresthesia who were anesthetized by Articaine.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Once again, the present study could not confirm the clinical superiority of articaine over lidocaine, which leads us to agree with Potocnik et al (17), who suggested that factors other than the anesthetic solutions and their concentrations could be responsible for IANB failure. Other explanations that may account for IANB failures include tachyphylaxis of the anesthetic solutions (19) and activation of nociceptors, including tetrodotoxin and capsaicin-sensitive transient receptor potential vanilloid type 1 (TRPV-1) receptors (19,20).…”
Section: Discussioncontrasting
confidence: 70%
“…Potocnik et al (17) studied the in vitro effects of lidocaine and articaine, both at concentrations of 2% and 4%, in addition to 3% mepivacaine, on decreases in the amplitude of the action potential produced by sensory nerve fibers in rats following supramaximal electrical stimulation. These authors reported that for all tested anesthetic solutions, there was complete disappearance of the action potential produced by the C-fibers but not the A-fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Potocnik et al [10] in an in vitro study concluded that 2 and 4 % articaine is more effective than 2 % and 4 % lidocaine or 3 % mepivacaine in depressing the compound action potential of the A fibers in the isolated rat sural nerve. In addition, the thiophene derivative (carticaine) blocks ionic channels at lower concentrations than the benzene derivative (lidocaine) [11].…”
Section: Discussionmentioning
confidence: 99%